2017
DOI: 10.3389/fpls.2017.00206
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Transcriptome Analyses Reveal Candidate Genes Underlying Yield-determining Traits in Brassica napus

Abstract: Yield is one of the most important yet complex crop traits. To improve our understanding of the genetic basis of yield establishment, and to identify candidate genes responsible for yield improvement in Brassica napus, we performed genome-wide association studies (GWAS) for seven yield-determining traits [main inflorescence pod number (MIPN), branch pod number (BPN), pod number per plant (PNP), seed number per pod (SPP), thousand seed weight, main inflorescence yield (MIY), and branch yield], using data from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 79 publications
1
64
0
Order By: Relevance
“…Based on protein–protein interaction study, OsLecRLK gene shows interaction with two important candidates domain with unknown function (DUF) protein and START. This DUF protein also interacts with α subunit of sucrose non‐fermenting related kinase‐1 (SnRK1) protein and acts as a mediator to bring SnRK1 protein closer to OsLecRLK (Lu et al, ). This OsLecRLK activates the SnRK1 protein by phosphorylating α subunit.…”
Section: Mechanismmentioning
confidence: 99%
“…Based on protein–protein interaction study, OsLecRLK gene shows interaction with two important candidates domain with unknown function (DUF) protein and START. This DUF protein also interacts with α subunit of sucrose non‐fermenting related kinase‐1 (SnRK1) protein and acts as a mediator to bring SnRK1 protein closer to OsLecRLK (Lu et al, ). This OsLecRLK activates the SnRK1 protein by phosphorylating α subunit.…”
Section: Mechanismmentioning
confidence: 99%
“…RNA‐Seq and GWAS both have their advantages, and combining them provides a powerful tool to discover not only active genes that express in response to treatments, but also genetic diversity and SNPs associated with the treatment. This combined strategy has been applied to understand white mold resistance and yields in B. napus (Lu et al., ; Wei et al., ) and soybean (Wen et al., ), but not in pea. Because genes that can be found by both GWAS and RNA‐Seq will have higher potential in contributing to white mold resistance, this study aimed to understand and compare the genetics of lesion and nodal resistance by applying both GWAS and RNA‐Seq approaches in the pea‐ S. sclerotiorum pathosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The desired traits vary among plants depending on the plant under study and the interest to a special or specific trait and the pertinent QTLs. QTLs have increasingly been reported in several studies such as plant height Brown et al (2008) Li et al (2015) Xu et al (2017), resistance to diseases Ayala et al (2002) Zhou et al (2015), seed size Zhang et al (2015), grain yield Vikram et al (2016), wood production in trees like Eucalyptus Rocha et al (2007), and higher yield Habyarimana et al (2017) Lu et al (2017).…”
Section: Qtlsmentioning
confidence: 99%
“…In order to improve yield in Brassica napus, a study reported that an integration of different methods as GWAS, DEGs and SNPs generate a promising output by which selection of rapeseed accelerates (Lu et al, 2017). The authors of this article have shown that candidate gene discovery is more accurate while using various datasets outputted by different methods and approaches and it is possible to determine which genes are key responsible genes involved in yield improvement of rapeseed.…”
Section: Genomic Selectionmentioning
confidence: 99%